Solidworks 2011 parts bible - Lombard, Matt (Wiley Publishing, 2011)
Provides information on creating parts in SolidWorks, covering such topics as working with sketches, using visualization techniques, modeling with primary features, patterning and mirroring, using equations, automating drawings, and dimensioning and tolerancing